Regional Macroeconomic Determinants of UMR - Rozzenda Risqi Shafa Hana; Sitti Retno Faridatussalam (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of regional macroeconomic conditions in shaping the Regional Minimum Wage (UMR) across five districts/cities in Central Java Province during the 2018–2023 period. Unlike prior studies that primarily focus on national indicators or limited economic variables, this research integrates fiscal capacity, social conditions, and human capital indicators within a regional panel data framework. The independent variables include Gross Regional Domestic Product (GRDP), poverty rate, number of Micro, Small, and Medium Enterprises (MSMEs), Regional Budget (APBD), number of investment projects, and educational participation. Panel data regression with the Random Effect Model (REM), selected through Chow and Hausman tests, is employed for analysis. The results show that all variables simultaneously have a significant effect on UMR determination. However, partially, only the poverty rate, APBD, and educational participation significantly influence UMR. A higher poverty rate is associated with increased UMR, indicating that wage policy responds not only to economic capacity but also to social pressure and welfare considerations. The positive effect of APBD highlights the importance of regional fiscal strength in supporting higher wage standards, while educational participation reflects the contribution of human capital quality to wage-setting mechanisms. In contrast, GRDP, MSMEs, and investment projects do not exhibit significant effects, suggesting that economic growth and investment do not automatically translate into higher wages at the regional level. This study contributes to the literature by demonstrating that UMR determination is more strongly driven by social and fiscal factors than by conventional growth indicators, emphasizing the need for region-specific, inclusive wage policies grounded in local macroeconomic realities.